Balancing Development and Heritage Conservation in Nepal: An Analysis With Reference to Legal and Policy Framework - Roka, Shreya (Unity Journal, 2024)
The confluence of infrastructural development and heritage conservation manifests a complex challenge in a least-developed country like Nepal, which celebrates its rich cultural legacy. The sustainable development of Nepal is affected by a lack of a proper legal and policy framework for balancing infrastructure development and heritage conservation. This research delves into the analysis of the existing laws and policies of Nepal, which have been legislated to create anequilibrium amidst the two. The research further investigates the gap in the legislation and practice in Nepal. Nepal has several national laws and ratified conventions like the Ancient Monuments Preservation Act in 2013, and the Convention Concerning the Protection of World Cultural and Natural Heritage, 1972, etc. which have not been well-implemented. Most of Nepal's legal and policy frameworks for heritage conservation are adaptations of international frameworks, which might not be appropriate in the context of the country. The thesis statement stresses that comprehensive, proportionate, and flexible legal and policy frameworks and their implementation can help achieve a delicate balance between infrastructure development and heritage preservation. Moreover, the research highlights the need for a multidimensional approach that considers the socio-cultural, economic, and environmental aspects of infrastructure projects while safeguarding Nepal's cultural heritage, emphasizing the need for ongoing refinement. The study uses doctrinal methods for data collection and analytical and descriptive approaches to data analysis. The findings of the study provide insights into the current situation and suggest recommendations for better balancing of infrastructure development and heritage conservation in Nepal.